Comparison of the Effectiveness of NocoDB and Nocobase Performance in the Development of Electronic-Based Government System Applications - Shelly Kurnia Ulisyah; Briansyah Setio Wiyono (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2025)
The implementation of government digitalization through the Electronic-Based Government System (SPBE) requires a fast and reliable application development platform. The low-code platform is an efficient solution, as it allows for application development with minimal coding. This research compares two open-source low-code platforms, NocoDB and NocoBase, focusing on performance effectiveness in supporting SPBE application development. Testing was conducted using K6 load testing with a configuration of 100 virtual users over the same duration. The results show that NocoDB has a higher throughput of 92.1 requests per second with a total of 2,763 requests, though accompanied by 86 failed checks, indicating response fluctuations under high load. In contrast, NocoBase recorded 33.3 requests per second with 100 successful requests and no failures, demonstrating more consistent response stability despite lower throughput. Thus, NocoDB is more effective for high-load scenarios, while NocoBase excels in service stability. These results are expected to serve as a technical reference in selecting the optimal low-code platform for the implementation of digital government systems based on SPBE.